A Buchwald–Hartwig Protocol to Enable Rapid Linker Exploration of Cereblon E3‐Ligase PROTACs. Issue 70 (3rd November 2020) - Hayhow, Thomas G.; Borrows, Rachel E. A.; Diène, Coura R.; Fairley, Gary; Fallan, Charlene; Fillery, Shaun M.; Scott, James S.; Watson, David W.
Abstract: A palladium‐catalysed Buchwald–Hartwig amination for lenalidomide‐derived aryl bromides was optimised using high throughput experimentation (HTE). The substrate scope of the optimised conditions was evaluated for a range of alkyl‐ and aryl‐ amines and functionalised aryl bromides. The methodology allows access to new cereblon‐based bifunctional proteolysis targeting chimeras with a reduced step count and improved yields. Abstract : PROTAC assembly : A method to introduce diverse amines to lenalidomide‐like scaffolds is described. The products from the Buchwald–Hartwig cross couplings could be used to access a range of PROTACs in a short number of subsequent steps. The coupling is effective from milligram to multigram scale.